Needs and preferences of patients with head and neck cancer in integrated care. (11th December 2017) - van Overveld, L.F.J.; Takes, R.P.; Turan, A.S.; Braspenning, J.C.C.; Smeele, L.E.; Merkx, M.A.W.; Hermens, R.P.M.G.; ,
Abstract : Objectives: Incorporation of patients' perspectives in daily practice is necessary to adapt care to users' needs. However, information on patients' needs and preferences for integrated care is lacking. The aim was to explore these needs and preferences, taking patients with head and neck cancer (HNC) as example, to adapt current integrated care to be more patient‐centred. Design: Semi‐structured interviews were held with current and former patients and chairmen of patient associations. Relevant needs and preferences were identified and categorised using the eight‐dimension Picker model of patient‐centred care. Setting: Integrated HNC in the Netherlands. Participants: Patients with HNC and chairmen of two Dutch HNC patient associations. Main outcome measures: Patients' needs and preferences of integrated HNC care categorised according the Picker model. Results: A total of 34 themes of needs and preferences were identified, by 14 patients with HNC or their delegates, using the Picker dimensions. Themes often emerged were as follows: personalisation of health care regarding patient values; clear insight into the healthcare process at organisational level; use of personalised communication, education and information that meets patients' requirements; adequate involvement of allied health professionals for physical support; more attention to the impact of HNC and its treatment; adequate involvement of family and friends; adequate general practitioner involvement in the aftercare; and waiting time reduction. Conclusions: Monitoring the identified themes in integrated HNC care, fitting in the Picker model, will enable us to respond better to the needs and preferences of patients, and patient‐centred care in oncological care can be enhanced.